China is implementing the national nutrition plan of action - Cai, Li; Hu, Xinyi; Liu, Shuang; Wang, Lei; Wang, Xuehong; Tu, Hua; Tong, Yeqing (Frontiers in Nutrition, 2022)
With the transformation of Chinese economic and social structure, the social determinants of nutrition have undergone significant changes, which have a great influence on the dietary patterns and nutrition status of its population. The transition in the structure of nutrition intake in China can be characterized by a rapid trend in food accessibility, affordability, and diversity. However, challenges, such as the triple burden of malnutrition (undernourishment, micronutrient deficiencies, and obesity), still seriously threaten the population's health. To approach the targets for the "Healthy China 2030", the General Office of the State Council of the People's Republic of China issued the National Nutrition Plan (2017-2030), which specifies multi-sectoral transdisciplinary measures to improve population nutrition status. In our study, we recognized the role of the National Nutrition Plan of China in responding to the call for the Sustainable Development Goals (SDGs). The study is the first attempt to understand China's nutrition action patterns. Under the global- and country-level targets, this paper presented six primary intervention measures highlighting the importance of collaborative actions for participants in all sectors.